Applying the theory of planned behaviour to littering prevention behaviour in a developing country (Nigeria). (1st April 2022) - Ojedokun, Oluyinka; Henschel, Nils; Arant, Regina; Boehnke, Klaus
Highlights: Littering has serious consequences for the environment and human wellbeing. Behavioral intention and perception of control influence littering prevention behavior. Littering intention mediated behavioral control and littering prevention behavior. Findings can help the development of TPB-based programmes to prevent littering. Implications for public policy and littering management are addressed. Abstract: Guided by the Theory of Planned Behaviour, this study investigates littering attitudes, social norms, and perceived behavioural control as predictors of the intention to prevent littering and actual littering prevention behaviour among residents of a developing country (Nigeria). The study employed a survey questionnaire to collect cross-sectional data. By applying structural equation modelling it was found that people who intend to prevent littering are also more likely to engage in actual littering prevention behaviour. At the same time, the perceived behavioural control had a significant influence on littering prevention intention. The study's findings can assist waste managers in formulating policies and interventions targeting behavioural intention and perceived behavioural control to foster littering prevention. Further, environmental managers should engage applied social and environmental psychologists or social scientists to design such behaviour change programmes.